Bacteriophage-based strategies for biocontrol and treatment of infectious diseases - Trinh Thi Trang Nhung; Swati Verma; Saravanaraman Ponne; Gautam Kumar Meghwanshi; Thomas Schön; Rajender Kumar (Computational and Structural Biotechnology Journal)
Bacteriophages are viruses that infect bacteria, which are essential for controlling bacterial diversity. Among the novel aspects, phage display-based strategies are used for epitope mapping and the development of immunotherapy. A recent classification system has been developed based on the recent sequencing methods and bioinformatic tools. The unique specificity of phages is of increasing use in biocontrol, where bacteriophages are applied to target and reduce harmful bacterial populations in agriculture, food preservation and safety, offering a sustainable alternative to chemical exposure and a plausible solution to excessive misuse of antibiotics. Phage therapy has emerged as a complement to antibiotics for difficult-to-treat infectious diseases such as multi-drug resistant bacteria where other alternatives are lacking. The ability of bacteriophages to specifically target pathogenic bacteria while sparing the normal flora makes them attractive treatment options. Among the challenges are the slow uptake of phage therapy in the clinical setting, a lack of standardisation and regulatory issues. Nevertheless, phage-based strategies are likely to become a future cornerstone for biocontrol and treatment of infectious diseases.